2008
DOI: 10.1002/pmic.200701048
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of Streptococcus pneumoniae TIGR4 response to in vitro iron restriction by 2‐D LC ESI MS/MS

Abstract: Understanding the growth of bacterial pathogens in a micronutrient restricted host environment can identify potential virulence proteins that help overcome this nutritional barrier to productive infection. In this study, we investigated the pneumococcal protein expression response to iron limitation using an in vitro model. We identified S. pneumoniae TIGR4 proteins by 2-D LC ESI MS/MS and determined significant changes in protein expression in response to iron restriction using computer-intensive random resam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 68 publications
3
22
0
Order By: Relevance
“…Proteomic analyses were carried out with proteins isolated from independent triplicate cultures of wild-type and DpotABCD and speE mutant strains. Proteins were trypsin-digested and desalted as previously described (Nanduri et al, 2008). Briefly, approximately 20 mg protein was reduced with 5 mM dithiothreitol at 65 uC for 5 min and alkylated with 10 mM iodoacetamide at 30 uC for 30 min.…”
Section: Proteomic Analysesmentioning
confidence: 99%
See 2 more Smart Citations
“…Proteomic analyses were carried out with proteins isolated from independent triplicate cultures of wild-type and DpotABCD and speE mutant strains. Proteins were trypsin-digested and desalted as previously described (Nanduri et al, 2008). Briefly, approximately 20 mg protein was reduced with 5 mM dithiothreitol at 65 uC for 5 min and alkylated with 10 mM iodoacetamide at 30 uC for 30 min.…”
Section: Proteomic Analysesmentioning
confidence: 99%
“…For protein identifications where gXcorr50 in a dataset, this method accounts for the discontinuity in identification by including a correction factor. We used a correction factor of 0.5 (Nanduri et al, 2008) for reporting the log 2 ratio of protein abundance.…”
Section: Proteomic Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Because iron-deprivation conditions are directly relevant to the host environment, several recent analyses of transcriptomic and/or proteomic profiles under iron-limiting conditions were performed to identify iron-responsive genes in Staphylococcus aureus [17], Mycobacterium tuberculosis [19], Streptococcus pneumoniae [20], Bacillus anthracis [21], and Listeria monocytogenes [22]. These studies revealed Fur- and/or DtxR-regulated genes as well as iron-responsive genes that may be controlled independently of these known iron-sensing metalloregulators.…”
Section: Iron Metalloregulation: a Pathogen’s Response To Host-inducementioning
confidence: 99%
“…Very recently, a combined translatomics/proteomics approach has been applied to 346 identify novel iron-transporting proteins in the pneumococcus (Yang et al 2016). Previously, 347 it had been approached using only proteomics (Nanduri et al 2008;Yang et al 2015). 348…”
mentioning
confidence: 99%